Epidemiological features of Echinococcosis in Russia - Dr Larisa Ermakova; Ms Maria Chernikova; Dr Tatyana Tverdokhlebova; Professor Sergey Kozlov; Professor Natalia Pshenichnaya; Professor Evgenia Chernikova (International Journal of Infectious Diseases)
Introduction: Echinococcosis is a serious problem in Russia, because foci of cystic (CE) and alveolar (AE) echinococcosis, which have medical significance, are registered on its territory. Due to the long asymptomatic period of the disease, epidemiological monitoring is difficult in conditions of active social migration of the population, and requires timely clinical, laboratory and instrumental examination. Methods: The study used data from official statistics, cards of an epidemiological survey of foci of echinococcosis (CESF) on the territory of the Russia over the past 7 years (2017-2023). Results: In 2017-2023, 2,790 cases of CE and 364 AE have been registered. An analysis of the dynamics of incidence per 100 thousand population showed a decrease in this indicator in 2020-2021 (0.16-0.19) by almost 2 in comparison with 2017-2019 (0.3-0.33). However, in 2023 the incidence increased again to 0.34. Discussion: An analysis over the past 7 years showed that higher incidence rates per 100 thousand population were recorded among rural residents. Analysis of the absolute numbers of cases showed that of the 2296 registered cases of CE in the Russia during the analyzed period, the majority (1815 cases, 79.1%) were urban residents.This is explained by the fact that the percentage of rural residents in Russia is about 25% of the total population. During the study period, 539 cases of CE were identified in Moscow alone (23.5% of all registered). A similar situation is observed with regard to AE, when out of 364 of all registered cases, 62.1% occurred among city residents (226 people). In Moscow alone, 61 cases (16.8%) were registered.The highest incidence rates of CE were registered in the Volga Federal District (25%). The largest number of cases of AE (66.2%) occurs in the Siberian Federal District (62%). The CE is the most widespread in Russia, but AE is of greater socio-economic importance. According to statistical reporting, the mortality rate of patients from CE ranged from 0 to 1.55%, while from AE from 2.08% to 11.3%.An analysis of CESF showed that the adult population accounted for 87.4% of cases of CE and 96.2% of AE. Working-age fertile population (18-49 years old) was predominant (64%). Echinococcosis of the liver was detected in 72.7% of cases, lungs - in 9.1%, rare localizations (muscles, spleen, brain, etc) were observed in 4.0%, combined echinococcosis – in 14.2%. Conclusion: The situation in Russia regarding echinococcosis remains unfavorable. The decrease in the incidence of echinococcosis in 2020-2021 is due to restrictive measures during the COVID-19 pandemic. Residents of rural areas remain at the highest risk of infection. High mortality rates from alveococcosis indicate late detection of this disease.